SENYAWA BIOAKTIF TORBANGUN (Plectranthus amboinicus (Lour.) SPRENG) FRAKSI KLOROFORM INDUKSI APOPTOSIS PADA KANKER PAYUDARA (SEL MCF-7) IN VITRO - Wahid Yulianto; Nuri Andarwulan; Puspo Edi Giriwono; Joko Pamungkas (Faculty of Pharmacy, Universitas Gadjah Mada, 2017)
Torbangun (Plectranthus amboinicus (Lour.) Spreng) is a medicinal plant that has been traditionally used in tropical countries to cure various illnesses. The objective of this study was to identify the active compounds in the chloroform fraction which have effect on the apoptosis-related genes expression of breast cancer MCF-7 cells. Apoptosis was observed morphologically using Hoechst nuclear staining. Expression of the genes was analyzed using Real-Time PCR. Chemical compounds of the plant fractions were determined using LC-MS. Result of cell morphology observation clearly indicated apoptosis after the treatment of the plant fraction. Increased expression of anti-apoptotic gene Bcl-2 could not prevent the cells from apoptosis. Expressions of p53 and p21 genes were increased significantly. The expressions of caspase 9, caspase 7 and caspase 1 were increased at concentration-dependent manner. Most of the compounds in the chloroform fraction are identified as diterpenoids which may contribute to the apoptosis inducing activity of the fraction.